2022
DOI: 10.1017/s0003055422000107
|View full text |Cite
|
Sign up to set email alerts
|

When Do Männerparteien Elect Women? Radical Right Populist Parties and Strategic Descriptive Representation

Abstract: Radical right populist (RRP) parties are often described as Männerparteien, predominantly led by, represented by, and supported by men. Yet recently, these parties have elected more women. Under what conditions do we see this increase in women MPs? This paper presents a novel argument of strategic descriptive representation: electorally struggling RRP parties with large gender gaps in voter support increase their proportion of women MPs to attract previously untapped women voters. To test this argument, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 94 publications
0
19
1
Order By: Relevance
“…On the other hand, some parties may use this effect strategically. For instance, populist radical-right partieswho are strongly disliked by mainstream partisans (Harteveld, Mendoza, and Rooduijn 2021; Helbling and Junkunz 2020; Reiljan and Ryan 2021)-may use women's representation to enhance their affective standing in the general public (see Weeks et al 2022). Given that opposition to extremist parties-particularly those that promote illiberal, antidemocratic stances-is arguably justified, it is troubling if these parties can defuse this hostility simply by promoting women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some parties may use this effect strategically. For instance, populist radical-right partieswho are strongly disliked by mainstream partisans (Harteveld, Mendoza, and Rooduijn 2021; Helbling and Junkunz 2020; Reiljan and Ryan 2021)-may use women's representation to enhance their affective standing in the general public (see Weeks et al 2022). Given that opposition to extremist parties-particularly those that promote illiberal, antidemocratic stances-is arguably justified, it is troubling if these parties can defuse this hostility simply by promoting women.…”
Section: Discussionmentioning
confidence: 99%
“…Political parties have even sought to capitalize on these beliefs. Weeks et al (2022), for example, argue that radical-right parties strategically increase their proportion of women MPs in order to defuse their extremist image and expand their support beyond their base. We thus posit the following:…”
mentioning
confidence: 99%
“…Parties may, for example, compose lists differently after an electoral loss, hoping to attract new voters with new - and possibly more diverse - candidates. Weeks et al (2023), for example, introduce a novel concept of strategic descriptive representation which suggests that parties will increase their number of women MPs after an electoral loss with large gender gaps in voter support to attract previously untapped women voters. They empirically confirm this strategy among European radical right populist parties.…”
Section: A Conceptual Multi-stage and Multi-actor Model Of Intra-part...mentioning
confidence: 99%
“…Research has shown that even the populist radical right party family, which is commonly characterized as staunchly anti-feminist and illiberal, is internally heterogeneous and nuanced in its positions on gender (Akkerman and Hagelund 2007;De Lange and Mügge 2015). If they are electorally struggling and suffering from a gender gap in voter support, radical right populist parties are more prone to engage in "strategic descriptive representation"-that is, to elect more women members of Parliament (MPs) to attract women voters (Weeks et al 2023). Kittilson's (2011) pioneering comparative study using party manifestos as empirical indicators of women's substantive representation was among the first to alert us that attention to women's interests transcends ideological blocs, as it is present in left-wing as well as right-wing party manifestos.…”
Section: Testing the Robustness Of The Rmp Novel Indicators: Three Hy...mentioning
confidence: 99%
“…Research has shown that even the populist radical right party family, which is commonly characterized as staunchly anti-feminist and illiberal, is internally heterogeneous and nuanced in its positions on gender (Akkerman and Hagelund 2007; De Lange and Mügge 2015). If they are electorally struggling and suffering from a gender gap in voter support, radical right populist parties are more prone to engage in “strategic descriptive representation”—that is, to elect more women members of Parliament (MPs) to attract women voters (Weeks et al 2023).…”
Section: The Study Of Gender Politics Using Parties’ Manifestosmentioning
confidence: 99%